Dongxiang Muslim women as ‘boundary subjects’: reflections on gender and identity in the borderland areas of northwest China - Man, Ke (Faculty of Social Sciences and Humanities, UKM,Bangi, 2010)
With the highest female illiteracy rate in China (2000 national census), the Dongxiang Muslim community in northwest China shows the most striking male-female gender hierarchy among all Muslim nationalities in northwest China. This paper explains how local Islamic culture – jiaopai and menhuan -- and the distinction made between Dongxiang (minority) and Han (majority) identity devalue women and restrict their mobility. Specifically, Dongxiang people are divided into different Islamic sects (jiaopai and menhuan or jiaomen), such as Beizhuang, Humen, and Santai. Most of them hold to their own sects and demonstrate negative evaluation of other jiaomen, so inter-jiaomen marriages are always forbidden. Women are the symbolic carrier of the jiaomen to which they belong, as can be seen in the distinctive head scarf (gaitou) women wear which signifies a given religious membership. To prevent their women from marrying out of the jiaomen and ensure integrity of the menhuan population, Dongxiang men constrain their women’s mobility. Gender also marks the ethnic boundary between Han Chinese (majority) and Dongxiang Muslim (minority) relations, legitimized by patriarchal interpretations of the holy scriptures which restrict women in the name of Allah. The paper argues that contemporary gender hierarchies in the Dongxiang community are not primarily moulded by Islam but by the cultural practices of a patriarchal society.